Research on the lead and tin contents and the activity of got and gpt in the blood of natives living in the mining region of the Son Duong tin mine, Tuyen Quang province - Hong Van, Luong Thi (Academia Journal of Biology, 2014)
The author reseached on the contents of lead and tin in the blood of natives living in the mining region of the Sonduong tin mine (Tuyenquang province). The results showed that the levels of lead and tin in blood of the natives in the first group were higher than in the control group from 1.5 to 2.1 times (p < 0.05). It seemed that there was a tight correlation between the levels of lead in blood and the activity of SGOT (serum glutamate oxaloaxetate transaminase) and SGPT (serum glutamate pyruvate transaminase) in these natives (r = 0.47 and r = 0.54, P < 0.05).